ENGLISH READING ANXIETY AMONG STUDENTS OF ENGLISH LANGUAGE EDUCATION STUDY PROGRAM AT UNIVERSITAS NEGERI GORONTALO INDONESIA - Aulianti Tuloli; Indri Wirahmi Bay; Helena Badu (Universitas Wiralodra, 2026)
This study examined the level and categories of English reading anxiety among students of the English Language Education Study Program at Universitas Negeri Gorontalo, class of 2023. Using a quantitative descriptive approach, the English Foreign Language Reading Anxiety Inventory (EFLRAI) by Zoghi (2012) was administered to 108 students through Google Forms. The instrument measured three categories of anxiety: top-down, bottom-up, and classroom reading anxiety. Data were analyzed using percentage formulas to classify responses into low, moderate, and high levels. Findings indicated that most students experienced moderate anxiety (56.48%), followed by high (37.04%), and only a small number reported low anxiety (6.48%). Bottom-up anxiety was the most dominant (96.30%), mainly due to vocabulary, while grammar had less impact. Top-down anxiety was linked to general reading ability (93.52%) rather than background & cultural knowledge (3.70%). Classroom reading anxiety was least significant (1.83%). These results highlight vocabulary mastery and general reading ability as major factors, suggesting the need for improved vocabulary teaching and reading strategies.